Analysis of thermal field within an urban canyon with variable thermophysical characteristics of the building's walls. (October 2015) - Vollaro, A De Lieto; Galli, G; Vallati, A; Romagnoli, R
Abstract: In a typical urban configuration, a microclimatic analysis has been carried out. Using a CFD method, a N-S oriented urban street canyon, with a given H/W ratio, has been examined. The standard k-ε turbulence model has been used to simulate a three-dimensional flow field and to calculate the thermo-fluid dynamics parameters that characterize the street canyon. In this study has been analyzed the thermal flow field when the walls of the building change the properties of solar radiation absorption, in particular for α=0.2 and α=0.8. Solar radiation considered is that of 21/07 in Milan in two different hours: at 11:00 a.m. and at 02:00 p.m. The study shows the importance of the thermophysical properties of a wall, in the development of the thermal field and flow field. This is a very important topic, in terms of improvement of wellbeing and the quality of the air within the cities, through the choice of materials and colors of the facades of buildings.